Long-term nexus of macroeconomic and financial fundamentals with cryptocurrencies - Pourpourides, Panayiotis M. (Frontiers in Blockchain, 2025)
We investigate the long-term impact of macroeconomic and financial factors on cryptocurrency metrics using both parametric and non-parametric methods. Our analysis examines how these factors influence cryptocurrency prices, market capitalizations, and Bitcoin’s hash rate. The results establish that two key factors, the US dollar and the price of gold, adversely affect Bitcoin and other cryptocurrency metrics, including the prices and market capitalizations of decentralized finance and layer-one protocols. Bitcoin’s hash rate demonstrates greater market sensitivity than its price, with the dollar having a stronger impact on Bitcoin than gold. The dollar primarily affects Bitcoin’s price, whereas gold mainly influences its hash rate. These findings, along with Bitcoin’s properties, support the view of Bitcoin as a digital asset analogous to physical gold, playing a role similar to a substitute for the latter.